Perspectiva distribuida del liderazgo y la gestión escolar: elementos e implicancias cruciales (Distributed perspective of leadership and school management: crucial elements and implications) - Spillane, James P.; Ortiz, Melissa (Revista Eletrônica de Educação, 2019)
Emphasizing that leadership practices are actions that are carried out among different people, in situations - which have norms, organizational routines and tools that define them - the authors insist on not considering leadership as an individual activity. It is emphasized that it is a work carried out by multiple people, with or without formal positions in the organizational structure and whose purpose is to focus on teaching and the disciplinary particularities of it. Another relevant concept analyzed in the text is the ‘educational infrastructure’ that considers the set of existing resources to sustain, maintain and improve the quality of teaching and pose some key challenges to realistically take a shared view of leadership practices in school. Resumo Enfatizando que as práticas de liderança são ações realizadas entre pessoas diferentes, em situações – que têm normas, rotinas organizacionais e ferramentas que os definem – os autores insistem em não considerar a liderança como uma atividade individual. Destaca-se que se trata de um trabalho realizado por múltiplas pessoas, com ou sem posições formais na estrutura organizacional e cujo objetivo é o foco no ensino e as particularidades disciplinares do mesmo. Outro conceito relevante analisado no texto é a “infraestrutura educacional” que considera o conjunto de recursos existentes para sustentar, manter e melhorar a qualidade do ensino e propor alguns desafios-chave para uma visão compartilhada das práticas de liderança escolar. Resumen Enfatizando que las prácticas de liderazgo son acciones que se realizan entre diferentes personas, en situaciones -que tienen normas, rutinas organizacionales y herramientas que las definen- los autores instan a dejar de considerar el liderazgo como una actividad individual. Subrayan que se trata de una labor que protagonizan múltiples personas, con o sin cargos formales en la estructura organizacional y cuyo foco ha de centrarse en la docencia y en las particularidades disciplinares de ésta. Otro concepto relevante analizado en el texto, es el de ‘infraestructura educativa’ que considera el conjunto de recursos existentes para sostener, mantener y mejorar la calidad de la enseñanza y plantean algunos desafíos clave para asumir con realismo una mirada compartida de las prácticas de liderazgo escolar. Keywords: School leadership, Shared leadership, Quality of teaching, Educational infrastructure. Palavras-chave: Liderança escolar, Liderança compartilhada, Qualidade do ensino, Infraestrutura educacional. Palabras claves: Liderazgo escolar, Liderazgo compartido, Calidad de la enseñanza, Infraestructura educativa. References BENNETT, N.; MARR, A. Judging the impact of leadership-development activities on school practice. Educational Forum, 67 (4), 2003, pp. 344-353. BRYK, A. S., SEBRING, P., ALLENSWORTH, E., LUPPESCU, S., & EASTON, J. Q. Organizing schools for improvement: Lessons from Chicago. Chicago: University of Chicago Press, 2009. BURCH, P. School leadership practice and the school subject: The Baxter case. In: J. P. SPILLANE; J. B. DIAMOND (Eds.), Distributed leadership in practice. Nueva York: Teachers College Press, 2007, pp.129-145. BURCH, P.; SPILLANE, J. P. Elementary school leadership strategies and subject matter: Reforming mathematics and literacy instruction. The Elementary School Journal, 103(5), 2003, pp. 519-535. CAMBURN, E. M.; ROWAN, B.; TAYLOR, J. E. Distributed leadership in schools: The case of elementary schools adopting comprehensive school reform models. Educational Evaluation and Policy Analysis, 25(4), 2003, pp. 347-373. COHEN, D. K. Teaching and its predicaments. Cambridge, MA: Harvard College, 2011. COHEN, D. K.; SPILLANE, J. P. Policy and practice: The relations between governance and instruction. Review of Research in Education, 18(3), 1992, pp. 3-49. COPLAND, M. A. Leadership of inquiry: Building and sustaining capacity for school improvement. Educational Evaluation and Policy Analysis, 25(4), 2003, pp. 375-395. CUBAN, L. The managerial imperative and the practice of leadership in schools. Albany, NY: SUNY Press, 1988. DEFLAMINIS, J. A.; ABDUL-JABBAR, M.; YOAK, E. Distributed leadership in schools: A practical guide for learning and improvement. Routledge, 2016. FIEDLER, F. E. A theory of leadership effectiveness. Nueva York: McGraw-Hill, Vol. 3, 1967. FROST, D. Resisting the juggernaut: Building capacity through teacher leadership in spite of it all. Leading and Managing, 10(2), 2005, p. 83. GIDDENS, A. Central problems in social theory (pp. 69). Londres y Basingstoke: The Macmillan Press Ltd., 1979. GONZÁLEZ, N.; MOLL, L. C.; AMANTI, C. Funds of knowledge: Theorizing practices in households, communities, and classrooms. Mahwah, NJ: Lawrence Erlbaum, 2005. GRISSOM, J. A.; LOEB, S. Triangulating principal effectiveness: How perspectives of parents, teachers, and assistant principals identify the central importance of managerial skills. American Educational Research Journal, 48(5), 2011, pp. 1091-1123. GRONN, P. Distributed properties: A new architecture for leadership. Educational Management Administration Leadership, 28(3), 2000, pp. 317-338. HALLETT, T. The leadership struggle: The case of Costen elementary school. In: J. P. SPILLANE & J. B. DIAMOND (Eds.), Distributed leadership in practice. Nueva York: Teachers College Press, 2007, pp. 85-105. HALLINGER, P. Instructional leadership and the school principal: A passing fancy that refuses to fade away. Leadership and Policy in Schools, 4(3), 2005, pp. 221-239. HALLINGER, P.; HECK, R. H. Reassessing the principal's role in school effectiveness: A review of empirical research, 1980-1995. Educational Administration Quarterly, 32(1), 1996, pp. 5-44. HARRIS, A. Effective leadership in schools facing challenging contexts. School Leadership & Management, 22(1), 2002, pp.15-26. HARRIS, A. Leading or misleading? Distributed leadership and school improvement. Journal of Curriculum Studies, 37(3), 2005, pp. 255-265. HAYTON, P.; SPILLANE, J. P. Professional community or communities? School subject matter and elementary school teachers' work environments. En: J. MACBEATH & Y. C. CHENG (Eds.), Leadership for learning: International perspectives. Rotterdam: Sense Publishers, 2008, pp. 65-79. HECK, R. H.; HALLINGER, P. Next generation methods for the study of leadership and school improvement. In: J. MURPHY & K. S. LOUIS (Eds.), Handbook of research on educational administration. San Francisco, CA: Jossey-Bass, 1999. HECK, R. H.; LARSEN, T. J.; MARCOULIDES, G. A. Instructional leadership and school achievement: Validation of a causal model. Educational Administration Quarterly, 26(2), 1990, pp. 94-125. HELLER, M. F.; FIRESTONE, W. A. Who's in charge here? Sources of leadership for change in eight schools. Elementary School Journal, 96(1), 1995, pp. 65-86. HEMPHILL, J. K. The leader and his group. Educational Research Bulletin, 28(9), 1949, pp. 225-229. HOPKINS, M.; SPILLANE, J. P. Conceptualizing relations between instructional guidance infrastructure (IGI) and teachers' beliefs about mathematics instruction: Regulative, normative, and cultural-cognitive considerations. Journal of Educational Change, 16(4), 2015, pp. 421-450. LEITHWOOD, K. A.; LOUIS, K. S.; ANDERSON, S.; WAHLSTROM, K. How leadership influences student learning: A review of research for the Learning from Leadership Project. Nueva York: The Wallace Foundation, 2004. LEITHWOOD, K. A.; MASCALL, B.; STRAUSS, T.; SACKS, R.; MEMON, N.; YASHKINA, A. Distributing leadership to make schools smarter: Taking the ego out of the system. Leadership and Policy in Schools, 6(1), 2007, pp. 37-67. LÓPEZ, A.; CORREA-CHÁVEZ, M.; ROGOFF, B.; GUTIÉRREZ, K. D. Attention to instruction directed to another by U.S. Mexican-heritage children of varying cultural backgrounds. Developmental Psychology, 46(3), 2010, pp. 593-601. MACBEATH, J.; ODURO, G. K. T.; WATERHOUSE, J. Distributed leadership in action: A study of current practice in schools. Nottingham: National College for School Leadership, 2004. MOLL, L. C. Some key issues in teaching Latino students. Language Arts, 65(5), 1988, pp. 165-472. PITTS, V.; SPILLANE, J. P. Using social network methods to study school leadership. International Journal of Research and Method in Education, 32(2), 2009, pp. 185-207. PORTIN, B.; SCHNEIDER, P.; DEARMOND, M.; GUNDLACH, L. Making sense of leading schools: A study of the school principal ship. Nueva York: The Wallace Foundation, 2003. PURKEY, S. C.; SMITH, M. S. Effective schools: A review. The Elementary School Journal, 83(4), 1983, pp. 427-452. PUSTEJOVSKY, J.; SPILLANE, J. P.; HEATON, R. M.; LEWIS, W. J. Understanding teacher leadership in middle school mathematics: A collaborative research effort. The Journal of Mathematics and Science: Collaborative Explorations, 11, 2009, pp. 19-40. ROBINSON, V. M. J.; LLOYD, C. A.; ROWE, K. J. The impact of leadership on student outcomes: An analysis of the differential effects of leadership types. Educational Administration Quarterly 44(5), 2008, pp. 635–674. ROSENTHAL, R.; JACOBSON, L. Pygmalion in the classroom. The Urban Review, 3(1), 1968, pp. 16-20. SHERER, J. Z.; SPILLANE, J. P. Constancy and change in school work practice: Exploring the role of organizational routines. Teachers College Record, 113(3), 2011, pp. 611-657. SILINS, H.; MULFORD, B. Schools as learning organisations: The case for system, teacher and student learning. Journal of Educational Administration, 40(5), 2002, pp. 425-446. SMYLIE, M. A.; DENNY, J. W. Teacher leadership: Tensions and ambiguities in organizational perspective. Educational Administration Quarterly, 26(3), 1990, pp. 235-259. SPILLANE, J. P. Primary school leadership practice: How the subject matters. School Leadership & Management, 25(4), 2005, pp. 383-397. SPILLANE, J. P. Distributed leadership. San Francisco: Jossey-Bass, 2006. SPILLANE, J. P. The practice of leading and managing teaching in educational organisations. In: OECD (Ed.), Leadership for 21st century learning: Educational research and innovation. París: OECD Publishing, 2013. SPILLANE, J. P. Leadership and learning: Conceptualizing relations between school administrative practice and instructional practice. Societies, 5, 2015, pp. 277-294. SPILLANE, J. P., CAMBURN, E., PUSTEJOVSKY, J., PAREJA, A. S., & LEWIS, G. Taking a distributed perspective in studying school leadership and management: The challenge of study operations. In: A. Harris (Ed.), Distributed leadership: Different perspectives. Dordrecht: Springer Press, 2009, pp. 47-80. SPILLANE, J. P.; COLDREN, A. F. Diagnosis and design for school improvement: Using a distributed perspective to lead and manage change. Nueva York: Teachers College Press, 2011. SPILLANE, J. P.; DIAMOND, J. B. Distributed leadership in practice. Nueva York: Teachers College Press, 2007. SPILLANE, J. P.; HALVERSON, R.; DIAMOND, J. B. Investigating school leadership practice: A distributed perspective. Educational Researcher, 30 (3), 2001, pp. 23-28. SPILLANE, J. P.; HEALEY, K. Conceptualizing school leadership and management from a distributed perspective. The Elementary School Journal, 111(2), 2010, pp. 253-281. SPILLANE, J. P.; HEALEY, K.; KIM, C. M. Leading and managing instruction: Using social network analysis to explore formal and informal aspects of the elementary school organization. In A. J. Daly (Ed.), Social network theory and educational change. Cambridge, MA: Harvard Education Press, 2010, pp. 129-156. SPILLANE, J. P.; HOPKINS, M. Organizing for instruction in education systems and school organizations: How the subject matters. Journal of Curriculum Studies, 45(6), 2013, pp. 721-747. SPILLANE, J. P.; HOPKINS, M.; SWEET, T. Intra- and interschool instructional networks: Information flow and knowledge production in education systems. American Journal of Education, 122, 2015, pp. 71-110. SPILLANE, J. P.; PARISE, L. M.; SHERER, J. Z. Organizational routines as coupling mechanisms: Policy, school administration, and the technical core. American Educational Research Journal, 48(3), 2011, pp. 586-620. SPILLANE, J. P.; SHIRRELL, M.; HOPKINS, M. Designing and deploying a professional learning community (PLC) organizational routine: Bureaucratic and collegial structures in tandem. Les dossiers des Sciences de l'Education, 2016, in press. TIMPERLEY, H. S. Distributed leadership: developing theory from practice. Journal of Curriculum Studies, 37(4), 2005, pp. 395-420 YUKL, G. An evaluation of conceptual weaknesses in transformational and charismatic leadership theories. The Leadership Quarterly, 10 (2), 1999, pp. 285-305.